2010
DOI: 10.1007/s13181-010-0103-9
|View full text |Cite
|
Sign up to set email alerts
|

Oral Glutamine Attenuates Cyclophosphamide-Induced Oxidative Stress in the Bladder but Does Not Prevent Hemorrhagic Cystitis in Rats

Abstract: Cyclophosphamide (CP) is widely used in the treatment of cancer and non-malignant disease states such as rheumatoid arthritis. Hemorrhagic cystitis is a major dose-limiting side effect of CP. The incidence of this side effect is related to the dosage and can be as high as 75%. Elimination of the side effects of CP can lead to better tolerance of the drug, and a more efficient therapy can be achieved for patients in need of CP treatment. Several studies have demonstrated that oxidative stress and neutrophil inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 32 publications
1
13
1
Order By: Relevance
“…In agreement with the present study, previous studies suggested that CP generates ROS like superoxide anion, hydroxyl radical and hydrogen peroxide during its oxidative metabolism and depresses the antioxidant defense mechanism in different tissues (Abraham et al, 2011;Senthilkumar et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with the present study, previous studies suggested that CP generates ROS like superoxide anion, hydroxyl radical and hydrogen peroxide during its oxidative metabolism and depresses the antioxidant defense mechanism in different tissues (Abraham et al, 2011;Senthilkumar et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…CP metabolites, and ROS generated in particular, can cause changes in cell redox balance, which leads to oxidative stress, resulting in cancer and healthy cell damage (Abraham et al, 2011;Jamshidzadeh et al, 2009). Moreover, superoxide radical may react with other radicals including nitric oxide producing peroxynitrite, in the cytosol and mitochondria (Mukhopadhyay et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Foxp3 + T cells are often recruited to a tumor before T eff cells are recruited, which prevents the T cell-mediated eradication of the tumor cells (60). Thus, the glutamine-deficient microenvironment of a tumor, potentially caused by the "addiction" of tumor cells to glutamine (61,62) or as an undesirable result of chemotherapy (32)(33)(34), appears to be a critical factor in enforcing a T reg cell phenotype even under conditions in which the CD4 + T cells recruited into the tumor are exposed to conditions that promote their differentiation into effectors. Manipulating the metabolic state of T cells may modulate the balance between effector and suppressor functions, potentially opening new avenues for the development of immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, quantitative metabolomics profiling has revealed that the intratumoral concentrations of glucose and glutamine are reduced in patients with hepatocellular carcinomas and stomach and colon tumors (29,30). Furthermore, alkylating chemotherapies decrease the intracellular generation of the antioxidant glutathione because of limited glutamine availability (31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…17 Previous investigation, which report increased levels of nitric oxide in liver of CP-treated rats; this could be credited to acrolein able to activate both ROS and NOx metabolite production with further production of superoxide anion, hydroxyl radical and hydrogen peroxide during CP oxidative metabolism leading to a depressed antioxidant defense mechanism in different tissues. 18 Increased levels of nitric oxide in liver of CP-treated rats; this could be credited to acrolein able to that decreased glycogen content could be related to the liver damage induced by the released lysosomal hydrolytic enzymes from the hepatocytes following a stimulated lipid peroxidation. 19 The cyclophosphamide induced hepatic histopathological changes.…”
Section: Histological Examinationmentioning
confidence: 99%